(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article presents and analyzes historical data on traditional methods and folk inventions used for air cooling in the buildings of Middle Eastern countries (Iran, Afghanistan, Pakistan, Tajikistan, Uzbekistan) with hot and dry climates during the summer season, and relevant conclusions are drawn.